A national industrial information system for small and medium scale industries in the Philippines - Aquino, Leticia E.; Vallejo, Rosa M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
The three major instruments used to develop, update and upgrade human skills and knowledge are education, training and information. They are recognized as important mechanisms for the transfer of knowledge especially in the field of industrial technology. Recognizing these vital instruments of industrial information in economic development, this study on the establishment of a National Industrial Information System has been done to systematize the effective and speedy informatin dissemination in industry.
The National Industrial Information System, as proposed is a network of agencies engaged in small and medium scale industry development. It is structured to include a center node that will coordinate information traffic between entities here and abroad. The center node is to be supported by several tentacles, with a minimum of ten and a maximum of fifteen information centers and libraries to compose the network. These 10 to 15 resource centers should have at least a sufficient collection of materials dealing with small and medium scale industry development. Furthermore, these resource centers should have an up-to-date subject index of all its materials, specifically on small-scale industries and its related subjects, published or unpublished. The supportive resource centers will be known as the Metro Manila Information Centers which reach out further to prospective end-users through the smaller Regional Information Centers in the regions. Finally, information goes to end-users through the Branch Information Centers, the basic units of the National Industrial Information System.
The study outlines the procedures in the setting up of an information system, identifying the Institute for Small-Scale Industries of the University of the Philippines as the Center Node. It defines the capabilities of the Institute to be the Center Node of the National Industrial Information System.
The plan also presents a cost analysis and budget program for the first two years.
Mimeographed.
Vita.
Thesis (Master of Library Science)--University of the Philippines Diliman
Keywords: Information storage and retrieval systems--Industry.